2013 IEEE 13th International Conference on Data Mining Workshops 2013
DOI: 10.1109/icdmw.2013.160
|View full text |Cite
|
Sign up to set email alerts
|

A Framework of Review Analysis for Enhancement of Business Decision Making

Abstract: In order to remain competitive, modern businesses must keep informed about consumers' opinions via web-based reviews or similar channels. Today, the usefulness factor in opinion mining is mainly achieved through helpful user ratings in reviews. Reviews belong to different categories and each category contains different types of information that have not yet been the focus of sentiment analysis research so far. There is useful content in each type of review that may be helpful to users as well as designers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Moreover, other sources such as Foursquare, TripAdvisor, Priceline, Orbitz, hotels.com, Epinions, MovieLens, and Expedia also use a source with only one paper, and so on are cited as spam detection sources which have (16%) of the total of studies. depicted in Figure (5). We observed that 37% of the papers adopt a support vector machine (SVM), 15% are Naïve Bayes (NB), and 9% are based on the k-nearest neighbors algorithm (k-NN).…”
Section: E Major Data Sources Of Spam Detection Studiesmentioning
confidence: 99%
“…Moreover, other sources such as Foursquare, TripAdvisor, Priceline, Orbitz, hotels.com, Epinions, MovieLens, and Expedia also use a source with only one paper, and so on are cited as spam detection sources which have (16%) of the total of studies. depicted in Figure (5). We observed that 37% of the papers adopt a support vector machine (SVM), 15% are Naïve Bayes (NB), and 9% are based on the k-nearest neighbors algorithm (k-NN).…”
Section: E Major Data Sources Of Spam Detection Studiesmentioning
confidence: 99%
“…All these types play a significant role in business decision making. In particular, an important aspect of every business is the effective analysis of information related to their product or service type, in order to prevail over competitors (Qazi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%